Nutrient digestibility and beef cattle performance fed by lerak (Sapindus rarak) meal in concentrate ration - Suharti, S.; Astuti, D.A.; Wina, E. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
This research was aimed to study the use of Lerak fruit meal to improve performance and feed digestibility of beef cattle. The research consisted of two trials (in vitro and in vivo studies). The in vitro trial was screening of bioactive compounds (saponin, tanin, dan diosgenin) in Lerak fruit (including seed) and continued to evaluate the effectivity of these compounds against ruminal protozoa. The in vivo study was done using 12 Ongole Crossbreed cattle which received 1of 3 different treatments: 1) concentrate without Lerak as control, 2) concentrate containing 2.5% Lerak, and 3) concentrate containing 5% Lerak. Anti protozoal activity, daily gain, and nutrient digestibility of beef cattle were measured. Results showed that saponin concentration in Lerak extracted by methanol was higher than that in Lerak extracted by water and Lerak meal, 81.5%; 8.2% and 3.85% respectively. Lerak extracted by methanol have higher antiprotozoal activity in vitro than Lerak extracted by water. In vivo experiment showed that there were no significant differences (P>0.05) of nutrient intake and digestibility in all treatments, that means the ration had good palatability and quality. Average daily gain of PO fed 2.5% Lerak was 20% higher than that of control diet (0.9 kg/day). Key words: Sapindus rarak, Protozoa, Performance, Ongole Crossbreed, Digestibility